UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETIL ASETAT DAUN BINAHONG (Anredera scandens (L.) Moq.) TERHADAP Shigella flexneri BESERTA PROFIL KROMATOGRAFI LAPIS TIPIS - Lilies Kusuma Wardhani; Nanik Sulistyani (Universitas Ahmad Dahlan, 2012)
Antibacterial compounds that can be used for the treatment of infections causedby bacteria. Traditionally, Anredera scandens is one of plant used as traditionalmedicine. The aims of this research are to find out the antibacterial activity of ethylacetate extract of Anredera scandens leaf and Minimum Bactericidal Concentration(MBC) against Shigella flexneri and to identify the chemical subtances of the ethylacetate extract found in Anredera scandens. The Anredera scandens leaf was extractedby use of maseration method using ethyl acetate as solvent. The antibacterial assay wasdone using liquid dilution method with varied concentration of Anredera scandens(8,5%, 8%, 7,5%, 7%, 6,5%, 6%, 5,5%, dan 5% w/v) to determine MBC.Chromatography test was done to identify the chemical substances of Anrederascandens extract. The result of this research showed that the MBC of Anrederascandens leaf extract was 8% w/v. The result of the phytochemical screening with tubetest and thin layer chromatogram showed that the extract of Anredera scandens leafcontained, polyphenols, and saponin.